The gravity oscillations of white dwarf stars - Brickhill, Anthony John (Department of Astronomy, 2016)
The numerical investigation of the oscillations of white dwarfs which is discussed below was begun at the suggestion of Professor Warner soon after the discovery of periodic variations in several cataclysmic variables. Its completion within a reasonable time was greatly helped by the availability of a computer program for the solution of the equations governing the structure of white dwarf stars provided by Dr W. B. Hubbard. Although the program could not be used in the original form for the present investigation, where the accuracy of the outer layers is critical, it provided an invaluable starting point and the coding of the equation of state of the core was used in an almost unaltered form.